Enforcement and compliance with fisheries regulations in Malaysia, Indonesia and the Philippines. - Viswanathan, K.K., Abdullah, N.M.R., Susilowati, I. and Siason, I.M. and Ticao, C. (Makati, Philippines ICLARM, 1997)
Fisheries Co-Management Project Research Report No. 5
Keywords: Fisheries; Philippines; Indonesia; Malaysia; Fisheries--Southeast Asia